If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.3 * 300 = x Multiply 0.3 * 300 90 = x Solving 90 = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 90 + -1x = x + -1x Combine like terms: x + -1x = 0 90 + -1x = 0 Add '-90' to each side of the equation. 90 + -90 + -1x = 0 + -90 Combine like terms: 90 + -90 = 0 0 + -1x = 0 + -90 -1x = 0 + -90 Combine like terms: 0 + -90 = -90 -1x = -90 Divide each side by '-1'. x = 90 Simplifying x = 90
| 0.03=6 | | 18(x-1)=12(x+3) | | 8x+10x=7 | | .3*300= | | 6(a+4)(a-7)=0 | | 7st+6su+8sv= | | X-6=7y | | 120=6x-6x | | 16x+4x=19+x | | n=5m+4 | | x+(x*.25)=183 | | (x^2+4x+4)(x^2-6x+9)=(-1) | | -3y-8=2y+17 | | (2x+39)+(x-7)+(x)=180 | | =4(a+9) | | (3r+8)(r-8)=0 | | log(x)=log(-2x+5) | | (15!)/(15-4)!4!•(.2^4)•(1-.2)^(15-4) | | 9-3(y-2)=3-3y | | 4x+5(-3)=10 | | 5x+2=-8+3x+20 | | 4v^2+0x-9=0 | | 13+16x=-5 | | 0.23-2.1x=-0.61 | | cos(x)+3x=0 | | 16=-6y+4(y+6) | | y(x-8)=5 | | -2[x-4]+7=-3 | | 15=logx | | x(.36)+y(.14)=.2 | | 16b^2-24b+9=0 | | 3+5(9+2n)=48+5n |